P38 mitogen-activated protein kinase activation in amygdala mediates κ opioid receptor agonist U50, 488H-induced conditioned place aversion. (21st April 2016) - Zan, G.-Y.; Wang, Q.; Wang, Y.-J.; Chen, J.-C.; Wu, X.; Yang, C.-H.; Chai, J.-R.; Li, M.; Liu, Y.; Hu, X.-W.; Shu, X.-H.; Liu, J.-G.
Highlights: κ opioid receptor activation induced significant conditioned place aversion in mice. p38 MAPK activated in the amygdala after U50, 488H pairing. Intra-amygdala injection of SB203580 blocked U50, 488H-induced conditioned place aversion. Abstract: κ opioid receptor agonists produce aversive effects in rodents, however the underlying mechanisms remain unclear. Activation of p38 mitogen-activated protein kinase (MAPK) has been discovered to play a critical role in the modulation of affective behaviors. The present study was undertaken to detect the possible involvement of p38 MAPK in the aversive effects induced by κ opioid receptor activation. We found that the κ opioid receptor agonist trans-(±)-3, 4-Dichloro-N-methyl-N-[2-(1-pyrrolidinyl)-cyclohexyl]benzenacetamide methanesulfonate salt (U50, 488H) produced significant place aversion in mice as measured by the conditioned place preference procedure, accompanied with significant p38 MAPK activation in the amygdala, but not in the nucleus accumbens and hippocampus. Stereotaxic microinjection of the p38 MAPK inhibitor 4-(4-fluorophenyl)-2-(4-methylsulfonylphenyl)-5-(4-pyridy-l)-1H-imidazole (SB203580) into amygdala significantly inhibited p38 MAPK activation and completely blocked the conditioned place aversion in mice. Thus, these results suggested that activation of p38 MAPK in the amygdala was required to mediate κ opioid receptor-induced aversive behavior.